DEVELOPMENTAL ADVANCES OF THE PARIHS FRAMEWORK OVER THE LAST DECADE: A CRITICAL INTERPRETIVE SYNTHESIS. (20th December 2022) - Berta, Whitney; Duan, Yinfei; Iaconi, Alba; Wang, Jing; Perez, Janelle; Song, Yuting; Chamberlain, Stephanie; Estabrooks, Carole
Abstract: The original Promoting Action on Research Implementation in Health Services (PARiHS) and i-PARiHS frameworks contend that the successful implementation of evidence-based practices is a function of the core elements evidence, context, facilitation, and the capacity of intended recipients to apply research to practice. While applied widely, a number of theoretical and practical challenges associated with the framework's application have been identified. Our critical interpretive synthesis examines how the last decade of research has advanced understanding of the conceptualizations of, relationships between, and dynamics amongst, PARiHS core elements. We find that work over the past decade affords more nuanced conceptualizations of context and facilitation; reveals myriad conceptualizations of implementation success, suggesting the need for a typology; demonstrates contradictory effects of context on facilitation that warrants more study; leads us to question the contextual primacy of leadership; and generally under-examines the interactions and dynamics amongst PARiHS core elements and their sub-elements.